The Role of the Wild Boar Spreading African Swine Fever Virus in Asia: Another Underestimated Problem - Cadenas-Fernández, Estefanía; Ito, Satoshi; Aguilar-Vega, Cecilia; Sánchez-Vizcaíno, José Manuel; Bosch, Jaime (Frontiers in Veterinary Science, 2022)
African swine fever (ASF) is a highly lethal infectious disease in naïve populations of domestic pigs and wild boar. In Asia, from the first outbreak in August 2018 until the end of November 2021, ASF has been reported in Asian countries. The ASF virus (ASFV) circulation in domestic pigs is considered the main problem in Asia. On the other hand, there are very few reports of ASF in wild boar. However, considering the high wild boar density within the same area of backyard domestic pig farms in Asia, the occurrence of ASFV infection in wild boar may be underestimated. The role of the wild boar in other ASF epidemiological scenarios, such as Europe, is key for the maintenance and transmission of the disease. Hence, we performed a preliminary study estimating the extent of ASFV infection in the Asian wild boar population. The potential risk area of ASF infected wild boar was calculated based on the habitat suitability for wild boar, the kernel density of ASF notification in backyard farms and wild boar, and the ASFV transmission rate of wild boar. As a result of the analysis, high, medium, and low-risk areas were identified throughout southeast and east Asia. The highest risk area was detected in China, followed by Myanmar, far east Russia, Thailand, Vietnam, Laos, Cambodia, and the Philippines. This study shows hot spots where a high risk of infection in wild boar is most likely to occur, helping to control ASF